I Survived the Japanese Tsunami, 2011 - Tarshis, Lauren; Dawson, Scott (New York, NY Scholastic Inc., 2013)
Visiting his dad's hometown in Japan four months after his father's death would be hard enough for Ben. But one morning the pain turns to fear: first, a massive earthquake rocks the quiet coastal village, nearly toppling his uncle's house. Then the ocean waters rise and Ben and his family are swept away -- and pulled apart -- by a terrible tsunami. Now Ben is alone, stranded in a strange country a million miles from home. Can he fight hard enough to survive one of the most epic disasters of all time?
Includes bibliographical references (pages 14-15).
Accelerated Reader
Reading Counts RC
Accelerated Reader AR
110605
Keywords: 2000-2099; Tohoku Earthquake and Tsunami, Japan, 2011 -- Juvenile fiction; Tsunamis -- Japan; Survival; Fathers -- Death; Historical fiction; Adventure fiction; Japan -- History -- 21st century; Action and adventure fiction; Historical fiction; History; Juvenile works